2013
DOI: 10.1093/jrr/rrt067
|View full text |Cite
|
Sign up to set email alerts
|

Is there room for combined modality treatments? Dosimetric comparison of boost strategies for advanced head and neck and prostate cancer

Abstract: The purpose of the study was to determine the dosimetric difference between three emerging treatment modalities—volumetric-modulated arc therapy (VMAT), intensity-modulated proton beam therapy (IMPT) and intensity-modulated carbon ion beam therapy (IMIT)—for two tumour sites where selective boosting of the tumour is applied. For 10 patients with locally advanced head and neck (H&N) cancer and 10 with high-risk prostate cancer (PC) a VMAT plan was generated for PTVinitial that included lymph node regions, deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…A wave of preclinical and clinical studies showed the potential of developing treatment targeting TLRs against prostate cancer. Based on these researches, one of the most probable approaches is to use agents targeting TLRs as adjuvants along with other treatments ( 67 , 68 , 71 , 77 , 78 ). Above all, elucidation of the mechanisms of cancer cell TLR signaling and crosstalk with other signaling pathways as well as the mechanisms of cancer progression will definitely provide a promising novel strategy for cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A wave of preclinical and clinical studies showed the potential of developing treatment targeting TLRs against prostate cancer. Based on these researches, one of the most probable approaches is to use agents targeting TLRs as adjuvants along with other treatments ( 67 , 68 , 71 , 77 , 78 ). Above all, elucidation of the mechanisms of cancer cell TLR signaling and crosstalk with other signaling pathways as well as the mechanisms of cancer progression will definitely provide a promising novel strategy for cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, advanced proton therapy [e.g. intensity-modulated proton therapy (IMPT)] has been adapted for irregularly shaped tumors, and the effect is beginning to examined by physical fundamental research [ 5 , 6 , 8 , 9 ]. The International Commission on Radiation Units and Measurements (ICRU) recommends defining proton therapy doses as the product of the relative biological effectiveness (RBE) and the physical dose of the proton, with its unit as Gy [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…EQD2 D50 to DIL were 110.7 Gy, 114.2 Gy and 150.1 Gy in IMAT, proton therapy and HDR BT plans, while the mean dose of the rectal wall was 30.5 Gy, 16.7 Gy and 9.5 Gy, and the mean dose to the bladder wall were 21.0 Gy, 15.6 Gy and 6.3 Gy, respectively. Georg et al examined the optimal radiotherapy technique in the radiotherapy of localised prostate cancer and stated that HDR and LDR BT techniques were clearly superior in terms of the bladder and rectal wall sparing, in contrast with IMAT, proton-and carbon-ion therapy, with the lowest values for HDR BT [2]. However, they did not examine the dose to the urethra.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 33,000 deaths from this disease will occur this year [1]. The standard of care in the curative treatment of low-and selected intermediate-risk prostate cancer is external beam radiotherapy with intensity-modulated arc therapy (IMAT) or with CyberKnife (CK) technique or interstitial high-dose-rate (HDR) or low-dose-rate (LDR) brachytherapy (BT) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation